Poly(ε-caprolactone)/siloxane biohybrids with applications in "smart windows" - Rodrigues, L. C. (2012)
In view of the potential technological impact of solid polymer electrolytes (SPEs) in the domain of solid-state electrochemistry, particularly in the production of advanced batteries, sensors and electrochromic and photoelectrochemical devices, the sub-class of SPE materials has attracted considerable interest during the last two decades. Li+-doped ormolyte systems obtained using the sol-gel method has been investigated in the last few years. In this study we have used conductivity measurements, cyclic voltammetry at a gold microelectrode and thermal analysis to characterize an electrolyte system based on a lithium perchlorate (LiClO4)-doped di-urethane cross-linked poly(ε-caprolactone)(PCL)/siloxane hybrid matrix. The PCL/siloxane host hybrid matrix represents an attractive alternative, as it is expected to have lower environmental impact than electrolytes currently used in commercial devices. The biocompatible, biodegradable and air-permeable properties of the PCL matrix have led to extensive application of this material in the manufacture of suture cord, artificial skin, re-sorbable prosthetic devices and as a container for drug delivery. The amorphous hybrid materials characterized in this study combine acceptable levels of ionic conductivity (9.58x10-6 and 2.53x10-4 S.cm-1 at 25 and 90 °C, respectively) with low environmental impact. The authors of a previous publication, have concluded that organic-inorganic systems based on poly(ε-caprolactone) may be used as dual-function electrolyte/adhesive component in prototype solid-state electrochromic devices. This component provides significant advantages in optical performance, cycle lifetime and durability of the electrochromic devices relative to conventional liquid electrolytes.